A single-center 18-year experience with oral candidiasis in Brazil: a retrospective study of 1,534 cases - Leandro Calcagno Reinhardt; Patricia da Silva Nascente; Juliana Silva Ribeiro; Adriana Etges; Rafael Guerra Lund (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract Despite the large number of published studies about oral candidiasis and associated risk factors, reports of large single-center retrospective studies on the prevalence of oral candidiasis, risk factors, and the oral candidiasis types diagnosed more frequently in oral diagnostic reference centers are scarce. The objective of the present study was to retrospectively survey the demographic and clinical profiles of 1,534 patients diagnosed with candidiasis and treated at the Center for Diagnosis of Oral Diseases (CDOD), Pelotas Dental School, Federal University of Pelotas between 1997 and 2014. Using a retrospective, cross-sectional, epidemiological design, data on race, gender, age, systemic diseases, oral candidiasis type and location, symptoms, and harmful habits such as smoking and alcohol consumption were collected. The statistical analysis was performed using STATA version 13.1. Risk factors for chronic atrophic candidiasis (CAC) were evaluated using Poisson regression with robust variance (p ≤ 0.05). The majority of patients with oral candidiasis seen at the CDOD over the 18-year period of analysis were Caucasian women, aged 51-60 years, nonsmokers, and nondrinkers, with no systemic disease, and who wore some form of dental prostheses. CAC was the single most common clinical type of candidiasis detected, and the most frequently affected oral site was the palate. These data from a large single-center in Brazil agree with previous evidence about the clinical and demographic profiles of patients with oral candidiasis.